2023
DOI: 10.2169/internalmedicine.1125-22
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-related Disease Emerging after COVID-19 mRNA Vaccination

Abstract: A 78-year-old Japanese woman with no history of rheumatic disease received 2 doses of the BNT162b2 COVID-19 mRNA vaccine. Two weeks later, she noticed bilateral swelling in the submandibular region. Blood tests showed hyper-immunoglobulin (Ig)G4emia, and 18 F-fluorodeoxyglucose (FDG)-positron emission tomography (PET) revealed the strong accumulation of FDG in the enlarged pancreas. She was diagnosed with IgG4-related disease (IgG4-RD) according to the American College of Rheumatology (ACR)/the European League… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Autoimmune-related thyroid and renal case reports include that of Graves’ disease following the second dose of the Pfizer COVID-19 vaccine [ 143 ] and “rapidly progressive IgA nephropathy” following the third dose of the Moderna COVID-19 vaccine [ 144 ]. A 78-year-old woman developed IgG4-related sialadenitis and autoimmune pancreatitis following her second Pfizer COVID-19 vaccine, the authors concluded: “the use of mRNA vaccines requires more studies regarding their effects on the human immune system” [ 145 ] (p. 1550).…”
Section: Evidence Of ‘Spikeopathy’—spike Protein Pathogenicitymentioning
confidence: 99%
“…Autoimmune-related thyroid and renal case reports include that of Graves’ disease following the second dose of the Pfizer COVID-19 vaccine [ 143 ] and “rapidly progressive IgA nephropathy” following the third dose of the Moderna COVID-19 vaccine [ 144 ]. A 78-year-old woman developed IgG4-related sialadenitis and autoimmune pancreatitis following her second Pfizer COVID-19 vaccine, the authors concluded: “the use of mRNA vaccines requires more studies regarding their effects on the human immune system” [ 145 ] (p. 1550).…”
Section: Evidence Of ‘Spikeopathy’—spike Protein Pathogenicitymentioning
confidence: 99%
“…This article reports a rare case of IgG4‐associated disease following COVID‐19 and a literature review of previous related case reports (Table 1). We found a total of six cases of IgG4 disease relevant to COVID‐19, three of which were new‐onset IgG4‐associated diseases following COVID‐19 vaccination and the remaining three following SARS‐CoV‐2 infection 2–7 . IgG4 disease does not target a specific organ and can present as pancreatitis, hepatitis, lymph node enlargement, or even tracheal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have indicated that COVID-19 vaccinations using mRNA or viral vector vaccines can trigger autoimmune diseases such as sialadenitis, autoimmune hepatitis (AIH), or autoimmune pancreatitis (AIP) in selected individuals [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. In the literature, several reports have treated the correlation between autoimmune pancreatitis and COVID-19 vaccination ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%